Increasing The Knowledge Of Women Of Reproductive Age About Prevention Behavior Of Sexually Transmitted Infections By Providing Education - Pratiwi Puji Lestari; Fika Aulia (OMNICODE Journal (Omnicompetence Community Developement Journal), 2023)
Sexually transmitted infections (STIs)/Sexually Transmitted Diseases (STDs) are infectious diseases which are a global reproductive health problem, because the pattern of the disease occurs in almost all countries. The purpose of this activity is to provide knowledge and provide education to adolescents to effectively improve STI prevention efforts. The design used is the provision of education through counseling and outreach about the dangers of STIs and how to prevent STIs. The questionnaire used is knowledge about the dangers of STIs and how to prevent STIs. The activity was carried out on May 8 2023 at the Posyandu in the Klayan Health Center, Banjarmasin City. From the results of the questionnaire it was known that the majority of participants were women of childbearing age in the age range of 20-35 years as much as 81.8%. Most of the participants were of reproductive age so they were more at risk of developing STIs. Provision of counseling materials is known to increase the knowledge of women of childbearing age. As many as 7 out of 11 participants experienced an increase in knowledge.